Isotopic composition of precipitation during strong El Niño–Southern Oscillation events in the Southeast Region of Brazil - dos Santos, Vinícius [UNESP]; Dias de Oliveira, Marcelo [UNESP]; Boll, Jan; Sánchez-Murillo, Ricardo; Menegário, Amauri Antonio [UNESP]; Gozzo, Luiz Felippe [UNESP]; Gastmans, Didier [UNESP] (Wiley, 2019)
Equatorial Pacific sea surface temperature variations interact with processes of atmospheric circulation, creating conditions for the occurrence of El Niño–Southern Oscillation (ENSO). ENSO events represent the most important interannual phenomena affecting climate patterns worldwide and causing significant socio-economic impacts. In the Brazilian territory, ENSO leads to an increase in drought episodes in the north-eastern region and an increase in precipitation in the southern region, whereas the effects over the south-east region are yet not well understood. The main goal of this study is to compare variations of isotopic composition in precipitation across the south-east portion of the Brazilian territory during two very strong ENSO events: 1997–1998 (ENSO 1) and 2014–2016 (ENSO 2). Daily isotopic records, available from the Global Network of Isotopes in Precipitation database for ENSO 1, and samples collected during ENSO 2 were used to compare the influence of both events on the isotopic composition of precipitation. Seasonal variations indicated more depleted precipitation during the wet seasons (δ 18 O = −5.4 ± 4.0‰) and enriched precipitation during the dry seasons (δ 18 O = −2.8 ± 2.3‰). Observed rainfall variations were associated with atmospheric large-scale processes and moisture transport from the Amazon region, whereas extreme values (enriched or depleted) appear to be associated with particular convective and stratiform precipitation events. Overall, more depleted isotopic composition of precipitation (δ 18 O = −4.60‰) and higher d-excess (up to +15‰) were observed during the dry season of ENSO 1 when compared with ENSO 2 dry season (δ 18 O‰ = −2.80‰, d-excess lower than +14‰). The latter is explained by greater atmospheric moisture content, particularly associated with recycling of transpiration fluxes from the Amazon region, during dry season of ENSO 1. No significant differences for δ 18 O and δ 2 H were observed during the wet season; however, d-excess from ENSO 2 was greater than ENSO 1, due to the slightly greater atmospheric moisture content and very strong upward motion observed. Our findings highlight the opportunity that environmental isotopes offer towards understanding hydrometeorological processes, particularly, the evolution of extreme climatic events of global resonance such as ENSO.
Keywords: ENSO; precipitation; Southeast Brazil; stable isotopes